2018
DOI: 10.1177/1357633x18775850
|View full text |Cite
|
Sign up to set email alerts
|

Personalised telehealth intervention for chronic disease management: A pilot randomised controlled trial

Abstract: Introduction The aim of this study was to assess the impact of home-based telehealth monitoring on health outcomes, quality of life and costs over 12 months for patients with diabetes and/or chronic obstructive pulmonary disease (COPD) who were identified as being at high risk of readmission to hospital. Methods This pilot study was a randomised controlled trial combined with an economic analysis to examine the outcomes of standard care versus home-based telehealth for people with diabetes and/or COPD who were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
67
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(68 citation statements)
references
References 22 publications
(26 reference statements)
1
67
0
Order By: Relevance
“…In this regard, a randomized controlled trial aiming to assess the effect of home telemonitoring systems on health, quality of life, and annual expenses of patients with diabetic and COPD, had revealed that during the utilization of this system, hospitalization expenses decreased, which compensated for the expense of implementing telemedicine. This study showed that telemonitoring had led to a higher quality of life for patients in the intervention groups while preserving the quality of services (9).…”
Section: The Aging Population and Chronic Diseasesmentioning
confidence: 68%
“…In this regard, a randomized controlled trial aiming to assess the effect of home telemonitoring systems on health, quality of life, and annual expenses of patients with diabetic and COPD, had revealed that during the utilization of this system, hospitalization expenses decreased, which compensated for the expense of implementing telemedicine. This study showed that telemonitoring had led to a higher quality of life for patients in the intervention groups while preserving the quality of services (9).…”
Section: The Aging Population and Chronic Diseasesmentioning
confidence: 68%
“…The lack of effect in this study is not unique, as current studies and reviews on the effects of remote monitoring on patient outcomes and health utilization have shown mixed results [ 16 - 18 ]. Some studies have reported positive results on some quality of life measures and symptoms [ 10 , 33 - 35 ], but many have reported no effects [ 8 , 12 , 36 - 39 ]. With respect to health care utilization, the effects are also mixed, with some reporting reductions in hospitalizations [ 5 , 7 , 33 , 40 - 42 ], length of stay [ 7 , 33 , 40 , 43 ], and ED visits [ 33 , 40 ], but many failing to find significant effects [ 6 , 10 , 34 , 36 - 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Remote monitoring programs are always monitored by a health care provider, even though they are sometimes referred to as self-management programs, as the recordings are taken by the patients [ 10 ]. Some remote monitoring programs also often have an educational component [ 11 , 12 ] such as coaching sessions to support self-management. COPD self-management behaviors include self-recognition and self-treatment of exacerbations (eg, taking medications); coping with breathlessness; and lifestyle changes such as quitting smoking, eating healthy, and exercising [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Development of new technology innovations and their different telemedicine applications in integrated care programs, such as teleassessments, have positive effects on the quality of care in chronic patients. 14,15,17,18 Although telemedicine has been shown to be useful for screening, diagnosis, and management in different studies, [19][20][21] there are still serious difficulties including deficiency of provider availability, community access to screening, and community demand for screening. 22,23 Challenges related to health care providers can involve scarcity in screening delivery or policies requiring a consultation from a family physician to access screening.…”
Section: Introductionmentioning
confidence: 99%